New Concept: Different Types of Insufficiency of the Saphenofemoral Junction Identified by Duplex as a Chance for a More Differentiated Therapy of the Great Saphenous Vein. (August 2013) - Stücker, M; Moritz, R; Altmeyer, P; Reich-Schupke, S
Even though the item 'saphenofemoral junction' (SFJ) is anatomically well defined, the incontinence of the SFJ is often incompetently described in clinical practice and studies. Especially with regard to the optimal therapy of the great saphenous vein, it might be of importance to have a more distinct regard to the SFJ as it is known that about 10–30% of the saphenous refluxes have no femoral origin. Considering the terminal and preterminal valve three types of incompetence of the SFJ may be differentiated: Type 1: Incompetent terminal, but competent preterminal valve; Type 2: Competent terminal, but incompetent preterminal valve; Type 3: Incompetent terminal and preterminal valve (complete incompetence). A review on prior studies and reports leads to the assumption that the differentiation of the distinct types of SFJ-incompetence allows a more individual and – perhaps – more effective therapy. Finally, studies are necessary to evaluate the here given new concept.